2002
DOI: 10.1046/j.1365-2036.2002.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mildly to moderately active ulcerative colitis with a tryptase inhibitor (APC 2059): an open‐label pilot study

Abstract: Background: Mast cells isolated from the colonic mucosa in active ulcerative colitis appear to be partially degranulated, suggesting the release of tryptase. Aim: To investigate the safety and activity of APC 2059, a highly specific tryptase inhibitor, in the treatment of ulcerative colitis. Methods: This was an open‐label, Phase 2, multicentre pilot study in patients with mildly to moderately active ulcerative colitis, with a disease activity index of 6–9 on a 12‐point scale. Fifty‐six adults received 20 mg A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…S1 and Movies S4 and S5). In support of our data, others have reported that 27 of the 56 UC patients that received the tryptase inhibitor APC-2059 improved clinically (28) and that the tryptase/kallikrein inhibitor nafamostat mesilate decreased mucosal inflammation in TNBStreated rats (29).…”
Section: Discussionsupporting
confidence: 79%
“…S1 and Movies S4 and S5). In support of our data, others have reported that 27 of the 56 UC patients that received the tryptase inhibitor APC-2059 improved clinically (28) and that the tryptase/kallikrein inhibitor nafamostat mesilate decreased mucosal inflammation in TNBStreated rats (29).…”
Section: Discussionsupporting
confidence: 79%
“…Because MCs from humans and other species release a variety of proteinases upon activation and degranulation, a link between MCs and PAR-2 activation has been suggested. Indeed, some data indicate that MC-derived proteinases can act as local activators of PAR-2, leading to PAR-2-mediated functional responses (22,29,33,46). In contrast, other work suggests that, because of NH 2 -terminal PAR-2 receptor glycosylation, MC-derived proteinases, like tryptase, are restricted in their ability to activate PAR-2 (6).…”
mentioning
confidence: 97%
“…The result of a pilot study has revealed that systemic administration of APC2059, a specific tryptase inhibitor, is safe and there is evidence of activity in the treatment of UC (41).…”
Section: Anti-proteinase / Par 2 Therapy In Colonic Mucosal Inflammationmentioning
confidence: 99%